Cultivating Physics Teacher Creativity through Local Wisdom-Based Learning Design - Habibi, Habibi; Nadi Suprapto; Setyo Admoko; Suliyanah; Utama Alan Deta; Munzulatur Rohmah (Journal of Dedication in Community, 2025)
This activity aims to foster physics teachers' creativity in designing contextual and meaningful learning by integrating local wisdom values ​​into the teaching and learning process through a community service program. The activity was implemented in Trenggalek Regency, targeting physics teachers who are members of the Physics MGMP. The implementation involved three main stages: (1) dissemination of local wisdom-based learning concepts, (2) mentoring in designing creative learning tools that integrate cultural elements and regional potential, and (3) reflection and evaluation of the learning design results. The results of the activity demonstrated an increase in teachers' understanding and skills in identifying local potential as a resource for physics learning, as well as their ability to package this information into engaging, innovative, and relevant media and learning scenarios for students. Furthermore, this training successfully fostered a collaborative spirit among teachers in developing creative learning ideas rooted in Trenggalek's local values, such as utilizing natural phenomena, traditional arts, and community activities as contexts for physics. Thus, this activity provides a real contribution in improving the professional competence of physics teachers and encouraging the realization of character-based and sustainable learning based on local wisdom